Discovery, Molecular Mechanisms, and Industrial Applications of Cold-Active Enzymes - Santiago, Margarita; Ramírez-Sarmiento, César A.; Zamora, Ricardo A.; Parra, Loreto P. (Frontiers in Microbiology, 2016)
Cold-active enzymes constitute an attractive resource for biotechnological applications. Their high catalytic activity at temperatures below 25 ºC makes them excellent biocatalysts that eliminate the need of heating processes hampering the quality, sustainability and cost-effectiveness of industrial production. Here we provide a review of the isolation and characterization of novel cold-active enzymes from microorganisms inhabiting different environments, including a revision of the latest techniques that have been used for accomplishing these paramount tasks. We address the progress made in the overexpression and purification of cold-adapted enzymes, the evolutionary and molecular basis of their high activity at low temperatures and the experimental and computational techniques used for their identification, along with protein engineering endeavors based on these observations to improve some of the properties of cold-adapted enzymes to better suit specific applications. We finally focus on examples of the evaluation of their potential use as biocatalysts under conditions that reproduce the challenges imposed by the use of solvents and additives in industrial processes and of the successful use of cold-adapted enzymes in biotechnological and industrial applications.